Implementation of Shared Services through ICT Budget Consolidation in the Ministry of Finance - Eni Sulistyowati, Eni; Hidayat, Yahya Rachmana; Komaruddin; Waluyo, Surryanto Djoko (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The government's ever-increasing Information and Communication Technology (ICT) spending is often inefficient due to duplication, silos, and separate management across work units. To address this, the Ministry of Finance implemented a shared services approach to consolidate the ICT budget. This study aims to evaluate the successful implementation of this program based on Burns and Yeaton's (2008) five success factors: strong project management capabilities, leadership support, effective communication, strong change management, and a phased implementation approach. The study used qualitative methods. The results indicate that the implementation of shared services successfully reduced duplication of ICT infrastructure by 65%, saved approximately IDR 350 billion in the first year of procurement, and accelerated the procurement process by up to 25%. However, challenges remain, such as the dynamics of human resource transfers that could potentially disrupt sustainability, the risk of losing momentum during phased implementation, and suboptimal consolidation due to the presence of two data centers, more than 300 applications, and limited interoperability. Recommendations include involving HR units in strategic ICT planning, competency regeneration through young human resources, application rationalization, data center consolidation, and the implementation of shared services nationally. This study contributes to strengthening integrated ICT management strategies in the public sector and provides policy recommendations to support digital government reform.